A 5 Gb/s CMOS adaptive equalizer for serial link *Project supported by the National Natural Science Foundation of China (No. 61376099), the Foundation for Fundamental Research of China (No. JSZL2016110B003), and the Major Fundamental Research Program of Shaanxi (No. 2017ZDJC-26). (April 2018) - Wu, Hongbing; Wang, Jingyu; Liu, Hongxia
Abstract: A 5 Gb/s adaptive equalizer with a new adaptation scheme is presented here by using 0.13 μ m CMOS process. The circuit consists of the combination of equalizer amplifier, limiter amplifier and adaptation loop. The adaptive algorithm exploits both the low frequency gain loop and the equalizer loop to minimize the inter-symbol interference (ISI) for a variety of cable characteristics. In addition, an offset cancellation loop is used to alleviate the offset influence of the signal path. The adaptive equalizer core occupies an area of 0.3567 mm 2 and consumes a power consumption of 81.7 mW with 1.8 V power supply. Experiment results demonstrate that the equalizer could compensate for a designed cable loss with 0.23 UI peak-to-peak jitter.